2023
DOI: 10.1002/smll.202303215
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance, Light‐Stimulation Healable, and Closed‐Loop Recyclable Lignin‐Based Covalent Adaptable Networks

Abstract: In this work, high‐performance, light‐stimulation healable, and closed‐loop recyclable covalent adaptable networks are successfully synthesized from natural lignin‐based polyurethane (LPU) Zn2+ coordination structures (LPUxZy). Using an optimized LPU (LPU‐20 with a tensile strength of 28.4 ± 3.5 MPa) as the matrix for Zn2+ coordination, LPUs with covalent adaptable coordination networks are obtained that have different amounts of Zn. When the feed amount of ZnCl2 is 9 wt%, the strength of LPU‐20Z9 reaches 37.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Preparation of LPU and LPU-G. According to our previous research, 21,22 lignin-based polyurethane CANs were synthesized with NCO/OH = 0.8. In the first step, the hydroxyl values of lignin-graphite composite particles and lignin were characterized using 31 P NMR.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of LPU and LPU-G. According to our previous research, 21,22 lignin-based polyurethane CANs were synthesized with NCO/OH = 0.8. In the first step, the hydroxyl values of lignin-graphite composite particles and lignin were characterized using 31 P NMR.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These nanocomposites demonstrated repeatable PTC behavior and allowed for reprocessing and closed-loop chemical recycling . Leveraging the polyhydroxyl groups on the surface of lignin, our previous studies have shown the successful preparation of lignin-based adaptable polyurethane networks (LPU) capable of exchange reactions without the use of a catalyst. , In this study, by incorporating lignin-graphite nanosheet composite particles, we obtained lignin-based stimulus-responsive polyurethane (LPU-G) with the LPTC effect. Furthermore, the utilization of biobased PDI and a significant amount of lignin endowed LPU and LPU-G with degradability.…”
Section: Introductionmentioning
confidence: 99%
“…249 Polyurethanes possess unique qualities that make them valuable, including low density, high strength-to-weight ratio, low thermal conductivity, low moisture permeability, and good dimensional stability. 250 The mechanical performance of polyurethane foams is classified based on their core densities and the use of stiff or semirigid polymers. In the study conducted by Wang et al 251 petrochemical polyols were partially substituted with alkali lignin during the develop PU.…”
Section: Poly Butylene Adipate-co-terephthalate (Pbat)mentioning
confidence: 99%
“…However, lignin can now be utilized to create a three-dimensional cross-linking structure that improves the material’s tensile strength and durability. , Polyurethanes made from biomass sources are more easily broken down by natural processes compared to those made from polyols derived from petroleum . Polyurethanes possess unique qualities that make them valuable, including low density, high strength-to-weight ratio, low thermal conductivity, low moisture permeability, and good dimensional stability . The mechanical performance of polyurethane foams is classified based on their core densities and the use of stiff or semirigid polymers.…”
Section: Application Of Lignin In Polymer Materials and Vanillinmentioning
confidence: 99%
“…Elastomers are widely used as substrates for fabricating flexible electronic devices as they possess excellent resilience performance and allow for excellent conformal contact with the body or internal organ surfaces to enable strain sensing with high sensitivity for potential applications in soft robotics, human–machine interfaces5, and healthcare. Electronic waste generated after service failure from wearable flexible devices causes serious pollution and has attracted widespread attention and deserves to be disposed of. Thermoplastic elastomer with physical cross-linking via supramolecular interaction such as hydrogen bonding, metal coordination, and ionic interaction or microphase separation structures combined by these interactions have been widely employed to fabricate healable and recyclable wearable electronic devices, but at the expense of sacrificing the resilience performance and creep resistance which has a big influence on the sensitivity and service stability of the fabricated devices. Chemical cross-linking of the elastomer via covalent bonds is capable of improving the resilience and dimension stability, but the challenge remains in achieving the recycling of the devices after service failure.…”
Section: Introductionmentioning
confidence: 99%